An epidemiological approach to study congenital Chagas' disease - Andrade Ana Lúcia S. S. de; Zicker Fabio; Martelli Celina M. T. (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1994)
Transplacental transmission of Trypanosoma cruzi has been the focus of much attention in highly endemic areas in South America. Frequency of congenital transmission and factors associated with risk of it are still not well understood. Parasite strains may account for part of the geographical variation observed. Methodological differences between the studies do not permit a combined interpretation of results. This paper examines the epidemiological data available from Brazil, Bolivia, and Argentina and discusses possible epidemiological study design to investigate risk factors for transmission.